Numerical Analysis of Unsteady Internal Flow Characteristics of Impeller-Guide Vane in a Vertical Axial Flow Pump Device - Yang, Fan; Chang, Pengcheng; Jian, Hongfu; Lv, Yuting; Tang, Fangping; Jin, Yan (Frontiers in Energy Research, 2022)
The vertical axial flow pump device has the characteristics of low head and large flow, and has various forms, simple structure and flexible installation. It is widely used in low head pumping stations in plain areas. In order to explore the transient characteristics of the internal flow in the impeller and guide vane of vertical axial flow pump at different flow rates, this paper analyzes the internal flow field distribution on the surface of the impeller blade, the velocity and pressure distribution of the impeller inlet and outlet, and the pressure pulsation characteristics of the impeller. The flow field characteristics of the guide vane section, the entropy production loss and the main frequency change of the pressure pulsation inside the guide vane are analyzed at different radius. The results show that under the condition of 0.8 Qbep, the streamline distortion area on the suction surface of the blade accounts for 11.5 % of the blade area, and the streamline distortion area on the pressure surface accounts for 14.4 % of the blade area. The streamline distortion area on the blade surface decreases significantly at 1.2 Qbep. The circumferential pressure distribution of the impeller inlet shows four high pressure regions and four low pressure regions, and the number of regions is consistent with the number of impeller blades. The ratio of axial force on the impeller under the three characteristic flow conditions of 0.8 Qbep, 1.0 Qbep and 1.2 Qbep is roughly 11:10:9. Radial force of impeller is not affected by flow rate. Under the condition of 0.8 Qbep, the radial force on the impeller is the largest, and its average value is 249 N. The fluctuation range of radial force is 60.2%-127.7% of the average value of radial force. The pressure pulsation amplitude in the guide vane gradually decreases from the inlet to the outlet of the guide vane, and the main frequency of the pressure pulsation at the inlet of the guide vane is four times the rotational frequency, while the outlet of the guide vane is not the blade frequency.